Fertility Intentions Across Five Decades in Norway - Dommermuth, Lars; Lyngstad, Torkild Hovde; Wiik, Kenneth Aarskaug (Comparative population studies, 2025)
Fertility intentions are strong predictors of future childbearing at both individual and aggregate levels, reflecting cultural norms and values around family formation and childbearing. Given the recent decline in fertility across Western industrialized societies, research on fertility intentions has become increasingly important. In particular, falling birth rates in the Nordic countries − traditionally held up as exemplars of modern family policies that balance work and parenthood − raise the question of whether women of childbearing age have experienced a shift in values related to family and childbearing. Using comparable survey data on Norwegian women aged 18 to 44 over five decades (1977, 1988, 2003, 2007, and 2020), we examine trends in fertility intentions. We consider short-term fertility intentions, defined as positive intentions to have a(nother) child within the next three to four years, as well as general fertility intentions, defined as positive intentions to have a(nother) child regardless of timing. We compare changes over the study period across demographic (age, parenthood, and partnership statuses) and socioeconomic (employment and education) groups. Our results reveal a gradual shift in short-term fertility intentions toward older age groups, reflecting changes in age-specific fertility rates and rising levels of childlessness. By 2020, both short-term and general fertility intentions had declined to their lowest levels over the study period − a trend that persisted even after controlling for key background characteristics. From 2007 to 2020, we observe a consistent decline in both types of fertility intentions across all sociodemographic groups. The decline in short-term fertility intentions began earlier among young women, childless women, women in education, and women without a co-residential partner − groups previously identified as experiencing sharper fertility declines after 2010 in the Nordic countries. The early and uniform downturn across key subgroups suggests that changing family values and life-course expectations may be driving the recent fertility decline.